Metaphors suggested by teachers and students on the concept of school health - Ozan, Mukadder Boydak; Ozdemir, Tuncay Yavuz (Academic Journals, 2010)
By virtue of this study conducted among teachers and students from the Technical and Vocational High Schools in Elazig province of Turkey, it has been aimed to identify their perceptions on the concept of school health. Within the framework of this general aim, participants were given blank questionnaires, including the statements, as School health is like ...; because ..., and asked to fill in these blank questionnaires. Workgroup of this study in the educational term of 2008-2009, is comprised of 34 teachers and 146 students from Gazi Technical and Vocational High School, located in Elazig Centrum. Study was conducted within the frame of content analysis model, being assessed within the paradigm of qualitative research. Upon reviewing each and every one of the answers given by the teachers and students, in response to the semi-structured, open-ended questionnaires they received, metaphors suggested respectively by the teachers and students were processed by analysts. Taking the views from 125 students out of the total of 146, and 30 teachers out of the total 34 into consideration, 88 valid metaphors from the students, and 29 from the teachers have been attained. Taking the generated metaphors list into consideration, it was examined how each metaphor conceptualized the concept of school health. At the next stage, correlating each metaphor image with a specific theme, a total of 10 different conceptual categories were attained. According to the outcomes, attained from the study, metaphors, being suggested by 47% of the teachers for defining school health as per their schools, were classified under the image of negativity, those, being suggested by 19.2% of the students for defining school health as per their schools, were classified under the well of life. Thus, metaphors, being suggested by students for defining school health, seem to reveal a much more optimistic nature, in comparison with those being suggested by teachers. It would be worthwhile to examine the professional exhaustion to the part of teachers, due to the negative developments to have occurred in their schools for the recent years.
Keywords: Metaphor; organization; school health; metaphors related with school health